Utilization of Oil Palm Empty Fruit Bunch in Cement Bricks - Jen Hua Ling; Yong Tat Lim; Wen Kam Leong; How Teck Sia (JACEE (Journal of Advanced Civil and Environmental Engineering), 2021)
Oil palm empty fruit bunch (EFB) is a biomass waste abundantly produced by the oil palm industry in Malaysia. To minimize the environmental impacts, it needs to be properly disposed of or being rapidly consumed as a raw material of another industry. This study investigated the feasibility of substituting EFB in cement bricks, which is in high demand by the construction industry. A total of 120 specimens having the cement-to-sand (c/s) ratios of 1:2.5 and 1:3 were produced in the laboratory. EFB fibre was used to replace 10% to 25% of sand in the mix by volume. The specimens were tested for the compressive strength, density and water absorption after 28 days of casting. For the mix of 1:2.5 c/s ratio, 25% EFB content reduced 22% of density, decreased 59% of compressive strength and increased 43% of water absorption capacity of normal cement brick. This was mainly attributed to the porous cellular structure of EFB fibre that created a large volume of voids in the mix. Based on the feasibility evaluation, EFB fibre can only replace up to 15% and 10% of sand in the mixes of 1:2.5 and 1:3 c/s ratios respectively.